Structural,optical and thermal properties of PVA/CdS nanocomposites synthesized by radiolytic method - Kharazmi, Alireza; Saion, Elias; Faraji, Nastaran; Mat Hussin, Roslina; Mat Yunus, Wan Mahmood (Elsevier, 2014)
Monodispersed spherical CdS nanoparticles stabilized in PVA solution were synthesized by the gamma radiolytic method and found the average particle size increased from 12 to 13 nm with the increment of dose from 10 to 40 kGy. The XRD results show that it has crystalline planes of cubic structure with crystal lattice parameter of 5.832 Å. The optical reflectance revealed a band-edge of CdS nanoparticles at about 475 nm and the reflectance wavelength red shifted with increasing dose due to increasing particle size. The thermal conductivity of CdS/PVA nanocomposites measured by the transient hot wire method that revealed a decrement of the thermal conductivity with an increase of dose caused by effect of radiation on crystallinity of the polymer structure.